Polyaniline graphene aerogel for catalytically degrading new pollutants in water and preparation method of polyaniline graphene aerogel

The polyaniline graphene aerogel catalyst synthesized through the frozen interface polymerization method solves the problems of secondary pollution and metal leakage in the persulfate system, and achieves efficient degradation and low-cost treatment of new pollutants in the water.

CN119113944AActive Publication Date: 2024-12-13TIANJIN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411263576.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The prior art has problems of secondary contamination and metal leakage in activated persulfate systems, and it is difficult to effectively degrade contaminants in complex emerging drugs and personal care products.

Method used

Polyaniline graphene aerogel (PANI/RGOT) was synthesized by frozen interface polymerization. Through hydrothermal synthesis and high temperature modification, a carbon-based catalyst with high specific surface area and conductivity was prepared for catalytic degradation of new pollutants in water. .

Benefits of technology

Deep degradation of bisphenol A is achieved, energy consumption and cost are reduced, and the catalyst can be recycled and used, avoiding secondary pollution, and the degradation rate reaches 88%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113944A_ABST
    Figure CN119113944A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon-based catalytic materials, and discloses polyaniline graphene (PANI / RGOT) aerogel for catalytically degrading new pollutants in water and a preparation method of the PANI / RGOT aerogel. The preparation method comprises the following steps: firstly, synthesizing a PANI / RGO original material by adopting a freezing interface polymerization method; after washing, performing ultrasonic treatment to uniformly disperse in water; carrying out hydrothermal synthesis on the dispersion liquid to obtain PANI / RGO aerogel, and freeze-drying the PANI / RGO aerogel; and carrying out high-temperature modification on the dried PANI / RGO aerogel to obtain the target product PANI / RGOT. The preparation operation is simple, the preparation condition is mild, the prepared aerogel material has the hexagonal honeycomb lattice layered structure of RGO and the high conductivity of PANI, the effect of persulfate for generating active oxygen is enhanced, bisphenol A can be effectively degraded, deep degradation of bisphenol A is achieved, recycling can be achieved, environment friendliness is achieved, secondary pollution is avoided, and the aerogel material is suitable for industrial production. Extra energy does not need to be consumed, and the method has wide practical application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon-based catalytic materials, and in particular, relates to a carbon-based catalytic material for catalytically degrading new pollutants in water and a preparation method thereof. Background Art

[0002] With the improvement of industrialization and urbanization, the types of pollutants in environmental water bodies have become more and more complex, and new pollutants contained in various emerging drugs and various personal care products (pharmaceuticals and personal care products, PPCPs) are also increasing. However, there are few types of microorganisms that can degrade such pollutants or they have not yet been domesticated, so most of these pollutants are difficult to biodegrade. At the same time, the current conventional water treatment process has limited effect on the treatment of PPCPs, so there is an urgent need for a technology to effectively treat such pollutants.

[0003] Persulfate advanced oxidation technology is a technology that uses persulfate (such as potassium persulfate, sodium persulfate, etc.) as an oxidant to generate strong oxidizing free radicals (such as sulfate free radicals, SO4 ·- ), thereby achieving efficient degradation and mineralization of organic pollutants. This technology is considered to be a better method for degrading PPCPs due to its high redox potential, long half-life, wider pH adaptability, and better selectivity. At present, the activation methods of persulfate advanced oxidation technology are mostly transition metal activation and external energy activation, which have the problems of high economic cost and easy secondary pollution. Graphene (GO) has good application prospects in the field of carbon-based catalysts due to its large specific surface area, high stability and easy adjustment of surface chemical properties, while pure graphene is catalytically inert and is not conducive to the catalysis of persulfate. Therefore, the development of a modified catalyst that has good PPCPs catalytic activity and environmental friendliness at low cost is a current research hotspot. Summary of the invention

[0004] The present invention aims at the technical problems of secondary pollution and difficulty in secondary recycling of homogeneous catalysts in activated persulfate systems, and the problem of metal leakage of metal heterogeneous catalysts in activated persulfate systems, and proposes a metal-free immobilized heterogeneous carbon-based catalytic material and a preparation method thereof. The catalytic material has the advantages of large specific surface area, convenient operation and easy recycling.

[0005] In order to achieve the above technical objectives, the present invention is implemented through the following technical solutions:

[0006] According to one aspect of the present invention, a polyaniline graphene aerogel for catalytically degrading new pollutants in water is provided, which is prepared by the following preparation method:

[0007] (1) Synthesize PANI / RGO raw materials by frozen interfacial polymerization;

[0008] (2) washing the PANI / RGO raw material obtained in step (1) and uniformly dispersing it in water by ultrasonication;

[0009] (3) synthesizing PANI / RGO aerogel by hydrothermal treatment of the dispersion obtained in step (2);

[0010] (4) freeze-drying the PANI / RGO aerogel obtained in step (3);

[0011] (5) The PANI / RGO aerogel dried in step (4) is subjected to high temperature modification to obtain the target product PANI / RGO T .

[0012] According to another aspect of the present invention, a method for preparing a polyaniline graphene aerogel for catalytically degrading new pollutants in water is provided, characterized in that the method comprises the following steps:

[0013] (1) Synthesize PANI / RGO raw materials by frozen interfacial polymerization;

[0014] (2) washing the PANI / RGO raw material obtained in step (1) and uniformly dispersing it in water by ultrasonication;

[0015] (3) synthesizing PANI / RGO aerogel by hydrothermal treatment of the dispersion obtained in step (2);

[0016] (4) freeze-drying the PANI / RGO aerogel obtained in step (3);

[0017] (5) The PANI / RGO aerogel dried in step (4) is subjected to high temperature modification to obtain the target product PANI / RGO T .

[0018] In the above-mentioned polyaniline graphene aerogel for catalytically degrading new pollutants in water and its preparation method:

[0019] Furthermore, the frozen interfacial polymerization synthesis in step (1) includes: placing a hydrochloric acid solution of ammonium persulfate in a -25--18°C ethanol temperature-controlled water bath, adding a GO dispersion dissolved by ultrasound after it is completely frozen, adding a pre-cooled hydrochloric acid solution containing aniline after it is completely frozen, and reacting at 0-2°C for 9-12 hours.

[0020] In step (1), preferably, the mass ratio of aniline to GO is 1:1-1:4.

[0021] In step (1), preferably, the molar ratio of aniline to ammonium persulfate is 1:0.5-1:2.

[0022] In step (1), preferably, the concentration of the mixed hydrochloric acid is 0.5-2 mol·L -1 .

[0023] Furthermore, the ultrasonication time in step (2) is 30-45 min.

[0024] Furthermore, the hydrothermal synthesis in step (3) is to place the dispersion obtained in step (2) in a hydrothermal kettle and react at 170-190° C. for 9-12 hours.

[0025] Furthermore, the freeze-drying time in step (4) is 12-24 hours.

[0026] Furthermore, the high temperature modification of step (5) comprises: placing the PANI / RGO aerogel obtained in step (4) into a tubular furnace, introducing nitrogen to remove oxygen, then heating to 900-1000° C., and maintaining the temperature for 1-2 hours, and then cooling to room temperature to obtain the target product PANI / RGO. T .

[0027] The beneficial effects of the present invention are:

[0028] The present invention uses aniline, graphene, and ammonium persulfate as raw materials, and sequentially adopts frozen interfacial polymerization, hydrothermal, high-temperature thermal reduction and other operations to prepare a carbon-based catalytic catalyst. The prepared catalytic material has high activity:

[0029] (I) Carbon-based catalyst PANI / RGO prepared by the present invention T Aerogel, which combines PANI and RGO made by frozen interfacial polymerization to form aerogel, has both the hexagonal honeycomb lattice layered structure of RGO and the high conductivity of PANI, and is easy to operate and has mild preparation conditions;

[0030] (II) Carbon-based catalyst PANI / RGO prepared by the present invention T Aerogel, using PANI with high conductivity, enhances the effect of persulfate in generating active oxygen;

[0031] (III) Carbon-based catalyst PANI / RGO prepared by the present invention T Aerogel can effectively degrade bisphenol A and achieve deep degradation of bisphenol A;

[0032] (IV) Carbon-based catalyst PANI / RGO prepared by the present invention T Aerogel can be recycled, is environmentally friendly, and has no secondary pollution;

[0033] (V) Carbon-based catalyst PANI / RGO prepared by the present invention T Aerogel does not require additional energy consumption, such as ultrasound, light, electricity, etc., which reduces costs and has broad practical application prospects;

[0034] In summary, the carbon-based catalyst PANI / RGO of the present invention T The aerogel and its preparation method are simple in preparation method and reduce energy consumption; the prepared catalyst further improves the effect of persulfate in generating active oxygen, and the degradation rate of bisphenol A can reach 88% in 60 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The PANI / RGO of the present invention T Flow chart of the preparation of aerogel catalytic materials;

[0036] Figure 2 PANI / RGO prepared in Example 1 T Image of aerogel catalytic material;

[0037] Figure 3 PANI / RGO prepared with different hydrochloric acid concentrations in Example 2 T Conductivity diagram of aerogel catalytic materials;

[0038] Figure 4 PANI / RGO prepared with different hydrochloric acid concentrations in Example 2 T Fourier infrared spectroscopy images of aerogel catalytic materials;

[0039] Figure 5 PANI / RGO prepared with different mass ratios in Example 3 T The effect of aerogel catalytic material on the degradation of bisphenol A;

[0040] Figure 6 PANI / RGO prepared at different thermal reduction temperatures in Example 4 T The effect of aerogel catalytic material on the degradation of bisphenol A;

[0041] Figure 7 PANI / RGO prepared in Example 4 T A diagram showing the degradation effect of aerogel catalytic materials on tap water containing bisphenol A. DETAILED DESCRIPTION

[0042] like Figure 1 As shown, the present invention provides a polyaniline graphene aerogel for catalytically degrading new pollutants in water and a preparation method thereof, which is prepared according to the following steps:

[0043] (1) The PANI / RGO raw material was synthesized by frozen interfacial polymerization at a reaction temperature of 0-2°C.

[0044] In some preferred embodiments of the present invention, a hydrochloric acid solution of ammonium persulfate is placed in a -25--18°C ethanol temperature-controlled water bath, and after being completely frozen, a GO dispersion dissolved by ultrasound is added, and after being completely frozen, a pre-cooled hydrochloric acid solution containing aniline is added, and the reaction time is 9-12 hours.

[0045] More preferably, the mass ratio of aniline to GO is 1:1-1:4; the molar ratio of aniline to ammonium persulfate is 1:0.5-1:2; and the concentration of hydrochloric acid after mixing is 0.5-2 mol·L -1 .

[0046] (2) After washing the PANI / RGO raw material obtained in step (1), it is evenly dispersed in water by ultrasonication.

[0047] In some preferred embodiments of the present invention, the ultrasonication time is 30-45 min.

[0048] (3) The dispersion obtained in step (2) is hydrothermally synthesized into PANI / RGO aerogel at a reaction temperature of 170-190°C.

[0049] In some preferred embodiments of the present invention, the hydrothermal synthesis is to place the dispersion obtained in step (2) in a hydrothermal reactor and react at 170-190° C. for 9-12 hours.

[0050] (4) freeze-drying the PANI / RGO aerogel obtained in step (3).

[0051] In some preferred embodiments of the present invention, the freeze-drying time is 12-24 hours.

[0052] (5) The PANI / RGO aerogel dried in step (4) is subjected to high temperature modification at 900-1000° C. to obtain the target product PANI / RGO T .

[0053] In some preferred embodiments of the present invention, the PANI / RGO aerogel obtained in step (4) is placed in a tubular furnace, nitrogen is introduced to remove oxygen, and then heated to 900-1000°C and maintained at this temperature for 1-2 hours, and then cooled to room temperature to obtain the target product PANI / RGO. T Finally, take out the material and store it in a dryer.

[0054] In a preferred embodiment of the present invention, the catalytic performance of the material as a catalyst is demonstrated.

[0055] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0056] Example 1

[0057] A method for preparing a polyaniline graphene aerogel catalytic material, the specific method steps are as follows:

[0058] In order to prepare highly conductive nitrogen-doped graphene, the study used the frozen interfacial polymerization method to in situ generate PANI on the surface of graphene oxide. First, a certain amount of aniline (AN) and ammonium persulfate were dissolved in 10 mL of hydrochloric acid (1 mol·L -1 ) solution, ultrasonically mix to obtain solutions of certain concentrations, which are recorded as solution A and solution B respectively. Then the aniline solution is placed in a 4°C refrigerator for precooling. At the same time, the ammonium persulfate solution is poured into a 100mL (inner diameter 40mm) double-layer screw-mouth bottle and placed in an ethanol temperature-controlled water bath at -18°C. After solution B is completely frozen, 20mL of graphene oxide solution containing 0.2g is poured into solution B, and the precooled solution A is poured after continuing to be water bathed at -18°C until it is completely frozen. Then the water bath temperature is adjusted to 2°C and the reaction is continued for 12h. After the reaction is completed, wash with ethanol and deionized water until the color no longer changes. The obtained solid is then ultrasonically dispersed in 20mL ultrapure water, placed in a 20mL reactor and reacted at 180°C for 12h, washed with ultrapure water for 5-6h after cooling, and freeze-dried at -80°C for 24h after precooling.

[0059] The freeze-dried material was placed in a tube furnace for thermal reduction. -1 At a flow rate of , nitrogen was introduced for 10 min to remove oxygen. -1 The temperature was heated to a certain temperature at a heating rate of 5 °C·min and maintained at the specified temperature for 1 h. -1 After the annealing rate reaches 300℃, it is naturally cooled to room temperature. After the cooling is completed, the obtained material is PANI / RGO. T The aerogel was stored in a desiccator away from light.

[0060] Figure 2 PANI / RGO T The picture of aerogel shows that the material is approximately cylindrical, with a diameter of about 2 cm and a height of about 3.5 cm.

[0061] Example 2

[0062] According to the method of Example 1, the hydrochloric acid concentration of solution A and solution B is 0 mol·L -1 , 0.25mol·L -1, 0.5mol·L -1 , 1mol·L -1 , 1.5 mol·L -1 , 2mol·L -1 Preparation of PANI / RGO T Aerogel catalytic material, PANI / RGO prepared with different hydrochloric acid concentrations T The electrical conductivity of aerogel catalytic materials is Figure 3 As shown, PANI / RGO prepared by different hydrochloric acid concentrations T Fourier infrared spectrum image of aerogel catalytic material Figure 4 shown.

[0063] from Figure 3 It can be seen that under a pressure of 1 MPa, the concentration of hydrochloric acid is 0-2 mol·L -1 In the range of 1 mol·L -1 The conductivity is highest when Figure 4 It can be seen that 1590cm -1 The peak at 1490 cm is the absorption vibration of the quinone skeleton N=Q=N of the polyaniline molecular chain. -1 The peak at 1290 cm corresponds to the absorption vibration of the benzene structure NBN. -1 The peak at 1170 cm is caused by the stretching vibration of aromatic amine CN. -1 and 810cm -1 The peaks at 810 cm-1 are the in-plane and out-of-plane bending vibrations of the benzene ring, and the peaks at 810 cm-1 are the in-plane and out-of-plane bending vibrations of the benzene ring. -1 There is only one peak at 0.5-2mol·L -1 The peak intensity of polyaniline prepared by hydrochloric acid solution system is higher than that of 0 mol·L -1 With 0.25mol·L -1 Sometimes it increases, especially at 1590cm -1 and 1490cm -1 The peak of the polyaniline molecular chain is significantly enhanced, indicating that its polymerization degree is improved. It can be seen that hydrochloric acid helps to improve the conductivity of polyaniline, but too high a hydrochloric acid concentration will inhibit the polymerization of aniline. -1 The conductivity of polyaniline prepared under hydrochloric acid concentration is good. Considering the factors of polymerization degree and hydrochloric acid dosage, 0.5 mol·L -1 Hydrochloric acid is the best method for preparing polyaniline.

[0064] Example 3

[0065] According to the method of Example 1, while maintaining PANI / RGO TUnder the condition that the mass of graphene remains unchanged during the preparation of aerogel, the mass ratio of aniline to graphene is changed by changing the mass of aniline. PANI / RGO is prepared with a mass ratio of aniline to graphene of 1:1, 1:2, 1:4, and 1:8, respectively. T Aerogel catalytic materials.

[0066] Taking bisphenol A as a typical new pollutant, the PANI / RGO with different mass ratios of aniline to graphene were obtained. T Aerogel catalytic material was used to degrade bisphenol A under the same conditions to explore the effect of the mass ratio of aniline to graphene on the degradation effect.

[0067] Add 100 mL of 5 mmol·L -1 10 mg·L of phosphate buffer solution (PBS) at pH = 7 -1 The bisphenol A solution was placed in a constant temperature oscillator with the temperature controlled at 25-30°C and the oscillation speed at 250 rpm·min -1 0.8 mL of the initial sample was taken, filtered through a 0.22 μm PTFE needle filter and placed in a 1.5 mL chromatographic bottle for instrument analysis; then 0.01 g of catalyst ([PANI / RGO T ]=0.1g·L -1 ) Start the pollutant adsorption test, take a sample every five minutes, take 0.8mL each time, take four times, filter each sample through a 0.22μm PTFE needle filter and put it into a 1.5mL chromatographic bottle for instrument analysis. After adsorption equilibrium, add 1.96mL of 50mmol·L -1 PDS ([PDS] = 1 mmol·L -1 ) to start the catalytic reaction, and sample 0.8 mL at 1, 2.5, 5, 10, 15, 20, 30, and 60 min, and filter through a 0.22 μm PTFE needle filter and put into a 1.5 mL chromatographic bottle for instrument analysis.

[0068] Figure 5 Shows PANI / RGO at different mass ratios T The effect of aerogel catalytic degradation of bisphenol A. With the increase of the mass ratio of aniline to graphene, PANI / RGO T The adsorption removal rate of aerogel for bisphenol A did not change much, but the adsorption removal rate was the highest at 1:2, which was 8.83%. The degradation efficiency generally showed a trend of increasing first and then decreasing, which was better at a mass ratio of 1:1-1:4 and the highest at 1:2, with a degradation efficiency of 61.46% in 60 minutes.

[0069] Example 4

[0070] According to the method of Example 1, PANI / RGO was prepared by thermal reduction at temperatures of 600°C, 700°C, 800°C, 900°C, and 1000°C. T Aerogel catalytic materials. Taking bisphenol A as a typical new pollutant, the PANI / RGO prepared at different thermal reduction temperatures T Aerogel catalytic material was used to degrade bisphenol A under the same conditions to explore the effect of thermal reduction temperature on the degradation effect.

[0071] Add 100 mL of 5 mmol·L -1 PBS 10mg·L -1 The bisphenol A solution was placed in a constant temperature oscillator with the temperature controlled at 25-30°C and the oscillation speed at 250 rpm·min -1 0.8 mL of the initial sample was taken, filtered through a 0.22 μm PTFE needle filter and placed in a 1.5 mL chromatographic bottle for instrument analysis; then 0.01 g of catalyst ([PANI / RGO T ]=0.1g·L -1 ) Start the pollutant adsorption test, take a sample every five minutes, take 0.8mL each time, take four times, filter each sample through a 0.22μm PTFE needle filter and put it into a 1.5mL chromatographic bottle for instrument analysis. After adsorption equilibrium, add 1.96mL of 50mmol·L -1 PDS ([PDS] = 1 mmol·L -1 ) to start the catalytic reaction, and sample 0.8 mL at 1, 2.5, 5, 10, 15, 20, 30, and 60 min, and filter through a 0.22 μm PTFE needle filter and put into a 1.5 mL chromatographic bottle for instrument analysis.

[0072] Figure 6 It shows that with the increase of thermal reduction temperature, PANI / RGO T The adsorption removal rate and degradation efficiency of aerogel for bisphenol A showed an increasing trend overall, and had a good degradation effect at 900°C and 1000°C. Among them, the adsorption removal rate at 900°C was 11.23%, and the degradation efficiency in 60 minutes could reach 76.27%.

[0073] The PANI / RGO prepared at 900°C in Example 4 T Aerogel catalyst was used to degrade tap water containing bisphenol A. -1 With potassium persulfate (PDS) as an oxidant, bisphenol A was used as a typical new pollutant and dissolved in tap water to explore the PANI / RGO T / PDS catalytic system on the degradation of bisphenol A in tap water.

[0074] Add 100 mL of 5 mmol·L -1 PBS 10mg·L -1 The bisphenol A tap water solution was placed in a constant temperature oscillator with the temperature controlled at 25-30°C and the oscillation speed at 250 rpm·min -1 0.8 mL of the initial sample was taken, filtered through a 0.22 μm PTFE needle filter and placed in a 1.5 mL chromatographic bottle for instrument analysis; then 0.01 g of catalyst ([PANI / RGO T ]=0.1g·L -1 ) Start the pollutant adsorption test, take a sample every five minutes, take 0.8mL each time, take four times, filter each sample through a 0.22μm PTFE needle filter and put it into a 1.5mL chromatographic bottle for instrument analysis. After adsorption equilibrium, add 1.96mL of 50mmol·L -1 PDS ([PDS] = 1 mmol·L -1 ) to start the catalytic reaction, and take samples at 1, 2.5, 5, 10, 15, 20, 30, and 60 minutes, taking 0.8 mL each time, filtering through a 0.22 μm PTFE needle filter and placing in a 1.5 mL chromatographic bottle for instrument analysis. The results are shown in the attached Figure 7 As shown, PANI / RGO T The adsorption removal rate of aerogel for bisphenol A is 14.34%, and the degradation efficiency can reach 88% in 60 minutes. Bisphenol A in tap water is basically removed, and the effect is quite obvious.

[0075] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims, all of which fall within the scope of protection of the present invention.

Claims

1. A polyaniline graphene aerogel for catalytic degradation of new pollutants in water, characterized in that: Obtained by the following preparation method: (1) Synthesize PANI / RGO raw materials by frozen interfacial polymerization; (2) washing the PANI / RGO raw material obtained in step (1) and uniformly dispersing it in water by ultrasonication; (3) synthesizing PANI / RGO aerogel by hydrothermal treatment of the dispersion obtained in step (2); (4) freeze-drying the PANI / RGO aerogel obtained in step (3); (5) The PANI / RGO aerogel dried in step (4) is subjected to high temperature modification to obtain the target product PANI / RGO T .

2. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 1, characterized in that: The synthesis by frozen interfacial polymerization method in step (1) comprises: placing a hydrochloric acid solution of ammonium persulfate in a -25--18°C ethanol temperature-controlled water bath, adding a GO dispersion dissolved by ultrasound after being completely frozen, adding a pre-cooled hydrochloric acid solution containing aniline after being completely frozen, and reacting at 0-2°C for 9-12 hours.

3. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 2, characterized in that: The mass ratio of aniline to GO is 1:1-1:

4.

4. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 2, characterized in that: The molar ratio of aniline to ammonium persulfate is 1:0.5-1:

2.

5. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 2, characterized in that: The concentration of hydrochloric acid after mixing is 0.5-2mol·L -1 .

6. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 1, characterized in that: The ultrasonic time in step (2) is 30-45 minutes.

7. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 1, characterized in that: The hydrothermal synthesis in step (3) is to place the dispersion obtained in step (2) in a hydrothermal reactor and react at 170-190° C. for 9-12 hours.

8. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 1, characterized in that: The freeze-drying time in step (4) is 12-24 hours.

9. The polyaniline graphene aerogel for catalytically degrading new pollutants in water according to claim 1, characterized in that: The high temperature modification of step (5) comprises: placing the PANI / RGO aerogel obtained in step (4) into a tubular furnace, introducing nitrogen to remove oxygen, then heating to 900-1000° C., maintaining the temperature for 1-2 hours, and then cooling to room temperature.

10. A method for preparing polyaniline graphene aerogel for catalytic degradation of new pollutants in water, characterized in that: The steps include: (1) Synthesize PANI / RGO raw materials by frozen interfacial polymerization; (2) washing the PANI / RGO raw material obtained in step (1) and uniformly dispersing it in water by ultrasonication; (3) synthesizing PANI / RGO aerogel by hydrothermal treatment of the dispersion obtained in step (2); (4) freeze-drying the PANI / RGO aerogel obtained in step (3); (5) The PANI / RGO aerogel dried in step (4) is subjected to high temperature modification to obtain the target product PANI / RGO T .

Citation Information

Patent Citations

  • Preparation method for polyaniline / graphene oxide nanocomposite

    CN104910378A

  • Preparation method of graphene polyaniline aerogel thermoelectric material

    CN106046401A

  • Catalyst for generating singlet oxygen through targeted activation of persulfate as well as preparation method and application of catalyst

    CN116139908A

  • Preparation method for polyamino three-dimensional graphene porous aerogel, and use thereof

    WO2023236699A2